Colloid and surface chemistry : a laboratory guide for exploration of the Nano world - Bucak, Seyda (CRC Press, Taylor & Francis Group, 2014)
With principles that are shaping today's most advanced technologies, from nanomedicine to electronic nanorobots, colloid and interface science has become a truly interdisciplinary field, integrating chemistry, physics, and biology. - Resumé vydavatel
Keywords: chemie povrchových jevů; koloidní chemie; surface chemistry; colloid chemistry; elektronické knihy; laboratorní cvičení; electronic books; laboratory manuals